2001
DOI: 10.1017/s004857720199016x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal signal bandwidth for the recording of surface EMG activity of facial, jaw, oral, and neck muscles

Abstract: Spontaneous pericranial electromyographic (EMG) activity is generally small and is contaminated by strong low-frequency artifacts. High-pass filtering should suppress artifacts but affect EMG signal power only minimally. In 24 subjects who performed a warned simple reaction time task, the optimal high-pass cut-off frequency was examined for nine different pericranial muscles. From four experimental conditions (visual and auditory reaction signals combined with hand and foot responses), 1-min EMG recordings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 0 publications
0
97
0
1
Order By: Relevance
“…The 100 Hz high-pass filter served to filter out artifacts (e.g. from eye movements) [35,36] and the 500 Hz low-pass filter is an antialiasing filter. EMG signals have both positive and negative values, so the mean was substracted from each signal to give a centered signal before full-rectification.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The 100 Hz high-pass filter served to filter out artifacts (e.g. from eye movements) [35,36] and the 500 Hz low-pass filter is an antialiasing filter. EMG signals have both positive and negative values, so the mean was substracted from each signal to give a centered signal before full-rectification.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…However, it is known that oversampling above this critical Nyquist rate does not significantly improve the signal quality [38], but will likely lead to higher cost and size of the sensor. The SEMG signals are usually bandpass filtered at 10-500 Hz [39], which we consequently chose to do for both setups. Furthermore, we observed that the notch filter, at 50 Hz, for the stationary equipment seemed to be saturated during recordings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Offline, EMG data were digitally bandpass-filtered from 20 Hz to 400 Hz [24] and rectified. Onset of EMG was automatically marked in each EMG-channel based on an amplitude threshold of 30 lV, and verified through visual inspection.…”
Section: Eeg and Emg Recordings And Analysesmentioning
confidence: 99%